A chip-on-board packaged bandpass filter using cross-coupled topological optimised hairpin resonators for X-band radar application. Issue 3 (March 2015) - Li, Yang; Wang, Cong; Kim, Nam-Young
Abstract Devices that are compact in design and fabrication continue to draw attention for specific applications that require high performance. A compact elliptic bandpass filter using a cross-coupled topological structure with a hairpin resonator optimised for radar applications is presented in this paper. This work presents the design theory and corresponding semiconductor fabrication processes and describes the chip-on-board packaging method in detail. The proposed design of the bandpass filter can not only reduce the size of the device and result in good RF performance, but the accurate semiconductor fabrication process can also ensure high performance further. In addition, the presented chip-on-board packaging method can greatly enhance the reliability and long-term stability of a microwave device, which rarely introduces RF characteristic interference. The simulated, bare-chip measured and final chip-on-board measured results agreed well, which validated the correctness of the proposed approach.